2007
DOI: 10.1007/s11102-007-0062-6
|View full text |Cite
|
Sign up to set email alerts
|

The long-term cardiovascular outcome of different GH-lowering treatments in acromegaly

Abstract: The aim of this longitudinal study was to evaluate the echocardiographic outcome of acromegalic heart disease in patients undergoing different therapeutic approaches, in order to investigate whether SSA could provide therapeutic advantages as compared with neurosurgery. In total of 36, consecutive patients undergoing SSA treatment after neurosurgery were enrolled in this study (Gr.Surg.-SSA). After 12 months of treatment, 21 patients had a controlled disease, while the remaining 15 patients displayed uncontrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
1
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 53 publications
5
28
1
1
Order By: Relevance
“…Although it is unlikely that a patient with biochemical control may show increase in tumor size during SSA treatment, it has been reported that tumor shrinkage may occur also in patients with ''biochemical'' resistance to lanreotide treated with a maximal dose of the drug [11][12][13], such as already reported in patients with prolactinomas treated with dopamine agonists [44]. Such a dissociation may be explained by a dose dependent effect of SSA on the tumor consistent with the hypothesis of a direct SSA effect, as previously suggested for other target organs such as the heart and bone [45][46][47]. Moreover, different mechanisms regulate the antimitotic and antisecretory actions of SSA [48,49].…”
Section: Discussionsupporting
confidence: 79%
“…Although it is unlikely that a patient with biochemical control may show increase in tumor size during SSA treatment, it has been reported that tumor shrinkage may occur also in patients with ''biochemical'' resistance to lanreotide treated with a maximal dose of the drug [11][12][13], such as already reported in patients with prolactinomas treated with dopamine agonists [44]. Such a dissociation may be explained by a dose dependent effect of SSA on the tumor consistent with the hypothesis of a direct SSA effect, as previously suggested for other target organs such as the heart and bone [45][46][47]. Moreover, different mechanisms regulate the antimitotic and antisecretory actions of SSA [48,49].…”
Section: Discussionsupporting
confidence: 79%
“…In general, the mortality rate of patients with DM or impaired glucose tolerance is significantly higher than in individuals with normal glucose tolerance [22] and its improvement or normalization in our patients may have contributed to their prolonged survival. Although our study did not evaluate its effect on cardiomegaly, in acromegalics, surgery has been reported to improve ventricular hypertrophy and cardiovascular functions [23,24]. According to Minniti et al 9 of their 11 surgically cured elderly acromegalics with left ventricular enlargement manifested postoperative normalization of the cardiac mass [4].…”
Section: Discussionmentioning
confidence: 77%
“…In this regard, however, it has been recently reported that treatment with somatostatin analogues, associated with neurosurgery, leads to additional improvement of cardiac parameters, when compared with neurosurgery alone (33). Therefore, it cannot be ruled out that the same positive effect of medical therapy could be observed also on SAS parameters if the sample size of medically treated patients, either in active or in inactive phase, was larger.…”
Section: Discussionmentioning
confidence: 98%